Perang Salib dalam Bingkai Sejarah - Syukur, Syamzan (Rihlah: Jurnal Sejarah dan Kebudayaan, 2014)
The Crusades were the Christians regarded as holy war (holy war), because it is seen as a war motivated by religious zeal , but the real motivation of religion in this war only take the smallest part compared with other motivations such as political and economic motivation motivation. Crusade between Muslims and Christians lasted for two centuries, and kemenanganpun alternated achieved by both parties. But the important notes in the event that the huge losses suffered by the people of the destruction of structures in both physical and social and psychological condition of the Muslims, because this war took place in the Islamic world. And instead provide a positive impact on the world, especially Europe to influence the progress of European civilization.